Pengaruh Lingkungan kerja Dan Pengembangan Karir Terhadap Loyalitas Kerja Pada PT. BANK BRI CABANG GORONTALO - ABUDI, SITTI; Yantu, Irwan; Bokingo, Agus Hakri (Jurnal Ilmiah Wahana Pendidikan, 2024)
The research aimed to determine the impact of work environment and career development on worker loyalty at PT. Bank BRI Branch of Gorontalo, to determine the impact of work environment on worker loyalty at PT. Bank BRI Branch of Gorontalo and to determine the impact of career development on worker loyalty at PT. Bank BRI Branch of Gorontalo. The research data were collected by distributing questionnaire and conducting observation. the research data were analyzed by using quantitative method. The research findings signified that partially, the work environment impacted the worker loyalty significantly for 56.8%, and so did the career development for 27.0%. Simultaneously, an R square value was 0.493, indicating that the worker environment and career development had a significant impact on worker loyalty by 49.3%. meanwhile, the rest 50.7% was impacted by other factors outside the variables studied, therefore further research is recommended to add other independent variables besides the one used in this research.